Desain dan Implementasi Model Strategi Pemasaran Berdasarkan Boston Matrix (Studi Kasus: Home Industry Flora Store Lamongan) - Prasetio, Ongky Aji; Puspitorini, Pipit Sari; Efendi, Imaduddin Bahtiar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyse the sales performance of two e-commerce platforms, Shopee and TikTok Shop, using sales data from Flora Store, a home-based perfume business located in Lamongan, East Java. In the face of increasingly fierce competition between digital markets, businesses such as Flora Store are utilising online platforms to reach a wider consumer base and increase sales. Sales data from April 2024 to March 2025 were analysed using Tableau software. The results of the analysis show that Shopee occupies the cash cow position due to its stable and dominant sales performance, while TikTok Shop is in the question mark position, as it has high growth rates but unstable sales. This study provides a strategic overview of the use of digital platforms in developing home industries and suggests the need for a more aggressive content marketing approach.